É POSSÍVEL ENSINAR ORALIDADE USANDO HISTÓRIAS EM QUADRINHOS? - Ramos, Paulo (Intercâmbio, 2010)
Is it possible to teach oral language using comics? We suppose that it’s perfectly possible. This is the main hypothesis of this communication and will be exemplified through the analysis and description of two different kinds of comics.